Human Fis1 regulates mitochondrial dynamics through inhibition of the fusion machinery - Yu, Rong; Jin, Shao‐Bo; Lendahl, Urban; Nistér, Monica; Zhao, Jian (The EMBO journal, 2019)
Mitochondrial dynamics is important for life. At center stage for mitochondrial dynamics, the balance between mitochondrial fission and fusion is a set of dynamin‐related GTPases that drive mitochondrial fission and fusion. Fission is executed by the GTPases Drp1 and Dyn2, whereas the GTPases Mfn1, Mfn2, and OPA1 promote fusion. Recruitment of Drp1 to mitochondria is a critical step in fission. In yeast, Fis1p recruits the Drp1 homolog Dnm1p to mitochondria through Mdv1p and Caf4p, but whether human Fis1 (hFis1) promotes fission through a similar mechanism as in yeast is not established. Here, we show that hFis1‐mediated mitochondrial fragmentation occurs in the absence of Drp1 and Dyn2, suggesting that they are dispensable for hFis1 function. hFis1 instead binds to Mfn1, Mfn2, and OPA1 and inhibits their GTPase activity, thus blocking the fusion machinery. Consistent with this, disruption of the fusion machinery in Drp1 −/− cells phenocopies the fragmentation phenotype induced by hFis1 overexpression. In sum, our data suggest a novel role for hFis1 as an inhibitor of the fusion machinery, revealing an important functional evolutionary divergence between yeast and mammalian Fis1 proteins. Synopsis Yeast Fis1 regulates mitochondrial dynamics by recruiting dynamin‐related fission factors, but the role of mammalian Fis1 has remained elusive. Human Fis1 (hFis) promotes Drp1‐ and Dyn2‐independent mitochondrial fragmentation by inhibiting mitofusins and OPA1 GTPase activity, revealing evolutionary divergence. Fission factors Drp1 and Dyn2 are dispensable for hFis1‐mediated mitochondrial fragmentation. hFis1 binds pro‐fusion mitofusins Mfn1 and Mfn2, and OPA1. hFis1 inhibits the GTPase activities of Mfn1, Mfn2, and OPA1, but not of Drp1 and Dyn2. Overexpression of hFis1 reduces mitochondrial fusion, whereas knockdown of hFis1 enhances mitochondrial fusion. Graphical Abstract Human Fis1 promotes Drp1‐ and Dyn2‐independent mitochondrial fragmentation by inhibiting mitofusins and OPA1 GTPase activity, revealing functional evolutionary divergence between yeast and mammalian Fis1 proteins.